Developed a unique technique for creating stable gold nanoparticles (AuNPs) to explore their potential against cancer - Anas S ALmomani; Ahmad Fairuz Omar; Ammar A. Oglat; Sarah Shakir Al-Mafarjy; Mohammed Ali Dheyab; Thair Hussein Khazaalah (South African Journal of Chemical Engineering, 2025)
Background: Gold nanoparticles (AuNPs) are frequently employed in biomedical science because to their inertness, small size, stability, biocompatibility, large surface area, and low toxicity. The crucial problem, however, is to produce non-toxic and biocompatible AuNPs. Unlike chemically manufactured AuNPs, laser ablation synthesis provides a non-toxic, easy, and cost-effective alternative. Objective: In this study, distilled water (DW) and Minimum Essential Medium (MEM) with phenol red are used to create small nanoparticles (NPs) with a narrower size distribution in highly stable colloidal NPs. The ability of these liquid media to replicate the spectral and size distributions of the synthesis of biocompatible AuNPs using laser ablation (LA) is also compared. Methods: We determined the sample size using Transmission Electron Microscopy (TEM). The AuNPs were synthesised in liquid form by adding several materials and compounds from MEM with phenol red and DW. Then, a laser was used to irradiate the target and ablate the metal plate. A drop of colloidal AuNPs was applied to a silicon wafer, which was then dried in an air oven to determine the materials' microstructural characteristics using a Field Emission Scanning Electron Microscope (FESEM). Energy Dispersive X-ray Spectroscopy (EDX) was used to evaluate the materials' elemental makeup. Furthermore, MCF-7 cells grown in DMEM media were used to test the cytotoxicity of the AuNPs using the MTT assay. Results: AuNPs in MEM with phenol red produced the smallest particles, size 8.84 nm at a wavelength of 532 nm, while AuNPs in DW produced particles size 16.3 nm at a wavelength of 1064 nm, as determined using TEM. These particle sizes were further confirmed by FESEM analysis, which showed closely comparable results, with AuNPs in MEM size 8.5 nm and those in DW size 18.6 nm. This difference is mainly due to physical and chemical properties and selecting a suitable laser wavelength with a limited absorption depth is critical to achieving efficient and rapid ablation with high-energy deposition in a small volume. Conclusion: The non-toxic process of laser ablation can be used to create biocompatible AuNPs, which may find use in cancer treatment. In order to improve their efficacy in targeted cancer treatment, future research should concentrate on controlling parameters and investigating media.